Effects of Sample Handling and Analytical Procedures on Thyroid Hormone Concentrations in Pregnant Women's Plasma. Issue 3 (May 2017) - Villanger, Gro Dehli; Learner, Emily; Longnecker, Matthew P.; Ask, Helga; Aase, Heidi; Zoeller, R. Thomas; Knudsen, Gun P.; Reichborn-Kjennerud, Ted; Zeiner, Pål; Engel, Stephanie M.
Abstract : Background: Maternal thyroid function is a critical mediator of fetal brain development. Pregnancy-related physiologic changes and handling conditions of blood samples may influence thyroid hormone biomarkers. We investigated the reliability of thyroid hormone biomarkers in plasma of pregnant women under various handling conditions. Methods: We enrolled 17 pregnant women; collected serum and plasma were immediately frozen. Additional plasma aliquots were subjected to different handling conditions before the analysis of thyroid biomarkers: storage at room temperature for 24 or 48 hours before freezing and an extra freeze–thaw cycle. We estimated free thyroid hormone indices in plasma based on T3 uptake. Results: High correlations between plasma and serum (>0.94) and intraclass correlation coefficients for plasma handling conditions (0.96 to 1.00) indicated excellent reliability for all thyroid hormone biomarkers. Conclusion: Delayed freezing and freeze–thaw cycles did not affect reliability of biomarkers of thyroid function in plasma during pregnancy. See video abstract at, http://links.lww.com/EDE/B180 . Abstract : Supplemental Digital Content is available in the text.